Barremian planktonic foraminiferal events correlated with the ammonite zones from the San Lucas Formation, Michoacán (SW Mexico) - Lourdes Omaña; Celestina González-Arreola; Blanca Margarita Ramírez-Garza (Revista Mexicana de Ciencias Geológicas)
We studied the Tiringueo section from the San Lucas Formation, located in the state of Michoacán, SW Mexico. The section is a ﬂysch sequence consisting of a rhythmic deposit of shale, siltstone, and ﬁne to medium graded sandstone interbedded with limestone. The sequence contains ammonites, foraminifera and radiolarians.